Profile of Leptin Levels in Schizophrenic patients Receiving Antipsychotic Therapy in Prof. Dr. HB Saanin Hospital Padang - Hasni, Dita; Sagala, Indah Cahya Aminta; Anissa, Mutiara; Eldrian, Febianne (Jurnal Kedokteran Brawijaya, 2020)
Weight-gain is one of the antipsychotic side effects, and it can increase the risk factor of metabolic syndrome. Several studies relate it to increase leptin levels. This research was conducted to determine the profile of leptin levels in schizophrenic patients who were receiving antipsychotic therapy at Prof. DR. HB Saanin Mental Hospital. The research was conducted from November 2019 to January 2020 on schizophrenic patients who were taking antipsychotic drugs. This research was conducted on 50 samples by using consecutive sampling techniques. Data analysis using univariate are presented in geometric mean and CI 95%. Moreover, a Comparison of leptin levels between groups was performed by T-test and one-way ANOVA. The average leptin level from 50 samples of schizophrenic patients was 5.12µg/ml (CI 95%=3.32-7.90). The highest average leptin level is from the 46-55 year age group which is 11.32µg/ml (CI 95% =5.24 - 24.42), female is  13.29µg/ml (CI 95%=5.84-30.26), BMI ≥30kg/m2  is 12.84µg/ml (CI 95%=4.31-38.23), subjects with above-average waist circumference is 5.54µg/ml ( CI 95%=3.45-8.90), and the atypical group of drugs is 6.08µg/ml (IK 95%=3.41-10.84). Increasing levels of leptin occur in schizophrenic patients who were 46-55 y.o, female BMI ≥30kg/m2, above-average waist circumference, and receiving atypical antipsychotics.